Evaluation of endometrial pathology in women with postmenopausal bleeding by saline infusion sonography and hysteroscopy - Bharti, Shikha; Dewan, Rupali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Postmenopausal bleeding (PMB) is a common problem representing 5% of all gynaecological outpatient attendance. Objective of this study was to determine diagnostic performance of saline infusion sonography and hysteroscopy for evaluation of endometrial lesions in postmenopausal bleeding. Methods: Being a prospective cross-sectional study, the present study was conducted on 46 postmenopausal women with bleeding, admitted to department of obstetrics and gynecology VMMC and Safdarjang Hospital, New Delhi, India. After TVS, all patients with ET >4 mm underwent SIS and then scheduled for hysteroscopy when there was no active bleeding. Sensitivity, specificity, positive predictive value and negative predictive value were calculated to compare the diagnostic accuracy of SIS and hysteroscopy. Results: Most commonly found endometrial lesions were polyp (39.13%) and endometrial hyperplasia (28.26%) among our study population consisting of 46 postmenopausal women (mean age 56.72±6.6 years). Overall sensitivity rates were 86.84% for SIS and 97.37% for hysteroscopy, while the overall specificity rates were 50% for both SIS and hysteroscopy. Hysteroscopy had PPV and NPV of 90.24% and 80% respectively whereas PPV and NPV were 89.19% and 44.44% for SIS. Conclusions: As an easy to perform, safe and well tolerated procedure yielding high diagnostic accuracy, SIS seems to be comparable to hysteroscopy for endometrial evaluation.